Когнітивні та вербальні обмеження формування словесних образів американської фольклорної балади - Суворова, Тетяна; Suvorova, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2015)
Автор статті акцентує основну увагу на основних когнітивних і вербальних обмеженнях формування словесних образів. Результати концептуального аналізу образності баладних творів узагальнено у вигляді моделей, які чітко вказують на можливості образного потенціалу баладних текстів. The paper studiesthe the word images functioning in American folklore ballad texts. The main cognitive and verbal limitations of a word image formation were evaluated. A comprehensive study of the imagery system of ballads was carried out. Particular attention was given to the conceptul level of the imagery. The primary aim of the investigation was to qualitatively describe various basic phrames emplied to the image formation and trace possible linguocognitive processes taking part in materialization of the images into words. The technique of а conceptual analysis along with a text interpritative one permitted to best evaluate the wide range of the ballad imagery conceptual schemata. The the case study of the imagery representing American folklore balladry was carried out from the view point of the imagery potential to function in the text. The results make it possible to plot integrated diagrams exposing the invariants of conceptual prospectives ot two main concepts of the investigated ballads. Deep understanding the ways the imagery system functions effects the degree of a successful text interpretation.
Cognitive And Verbal Limitations Of Imagery Formation In American Folklore Ballad Texts.
Keywords: словесний образ; концептуальна схема; базовий фрейм; лінгвокогнітивний процес; word image; conceptual scheme; basic frame; linguocognitive process